Bwah Loka in Sarad Pulagembal as an Idea for Creating Sculpture - Tenaya, I Made Suwardana; Mustika, I Ketut; Jodog, I Made (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2024)
The yadnya ceremony in Bali cannot be separated from an upakara or offering. One of the upakara or offerings that contains a touch of artistic elements is Sarad Pulagembal. Sarad Pulagembal is made from rice flour dough given various colors, symbolizing the positive powers of Bhuwana Agung. In Sarad Pulagembal there are components that are distributed according to the position in the Tri Loka, namely from bottom, to middle, to top (Bhur, Bwah, Swah). Bhur Loka is the layers of negative natural dimensions, Bwah Loka is the layers of the cycle of life and death, Swah Loka is the layers of positive natural dimensions. In the middle part (Bwah Loka) depicts elements of the living world such as humans and animals, the sarad pulagembal will of course contain these elements. The aim to be achieved in the creation of this work is to find out the contents of Sarad Pulagembal, especially in the middle part (Bwah Loka) and it will be developed with creativity and imagination into the form of a sculptural work of art using elements of fine art, such as color, media and techniques. . In the process of realizing this work, the author used interview, observation and experiment methods. From the theme above, 5 (five) sculpture works will be created entitled Purusa, two works entitled Pradana, three works entitled Tunjung, four works entitled Angsa, and five works entitled Boma.